Strategies to Increase Visitors by Developing Aspects of Attractions in Alam Santosa - Bintang Nugraha; Ranti Rachmawanti (Jurnal Indonesia Sosial Teknologi, 2024)
Traditional games are an integral part of Indonesian culture and have been passed down from generation to generation. Traditional games have a positive impact on child development, but are currently facing considerable challenges due to the rapid development of technology that has changed the interests of the millennial generation. To ensure the preservation of traditional games, several conservation efforts have been made, such as integrating traditional games into the concept of desa wisata. The concept of desa wisata is a significant trend in the tourism industry. In addition to presenting an authentic experience, a desa wisata can illustrate the unique life and traditions of rural communities, for example Alam Santosa in Cikadut Village. Alam Santosa was established to introduce culture with a number of buildings with Sundanese architecture and typical West Javanese art. One of the tourism products featured at Alam Santosa is cultural education in the form of playing traditional games or commonly referred to as kaulinan barudak. However, currently the availability of attractions and amenities at Alam Santosa has not provided a positive experience for visitors. This research was conducted to answer the solution of improving the visitor experience at Alam Santosa by utilizing the surrounding potential to provide an authentic experience. The result of the design that has been carried out is the development of bebedilan with the concept of building-games to provide a positive experience that can be proven by a visitor satisfaction rate of 90%.